THE EFFECT OF CREATIVE PROBLEM SOLVING METHOD TOWARDS EFL STUDENTS’ READING COMPREHENSION - Eka Wilany; Abdul Rahman (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
Reading is very important when someone study about language specifically English..EFL Students must have good reading skill to understand the meaning in a text. Most of the tests faced by students at school need the comprehending skill. Moreover, Creative Problem Solving method can empower teams of teachers and students to work together to meet the challenges of educating a heterogeneous school population. The objective of this research was to find out whether there was significant effect of Creative Problem Solving method towards students’ reading comprehension. This research was quantitative experimental research. The design was nonrandomized control group, pretest - posttest design. The samples were two classes in SMAN 11 Batam. It was used total sampling. Multiple choice of reading comprehension test was used as instrument of this research. The result showed that the t-observed is 3,98 and t-table is 2.00. It means that t-observed is higher than t-table, Ha is accepted and H0 is rejected. The research found out that there was significant effect of Creative Problem Solving Method to students’ reading comprehension. By using creative problem, student found the problem they found and think the best solution for their problem.